Catheter tip cultures on open-heart surgery patients: associations with site of catheter and age of patients. - Freeman, R (Thorax, 1981)
The results of culture of 668 catheter tips from 422 patients are analysed with relation to the site of the catheter and the age of the patient. Coagulase-negative staphylococci were the most common bacterial isolate, but Gram-negative bacilli were found in the venous lines, femoral artery lines, and peripheral lines. Isolations of Gram-negative bacilli were associated with age, being found mainly in those under 1 year and those over 40 years of age. Typing of coagulase-negative staphylococci revealed that Staphylococcus epidermidis is the only variety found in peripheral lines and in lines inserted after operation for complications (central venous, sub-clavian, and long lines), whereas other types occur (along with Staphylococcus epidermidis) in the other lines (left atrial, arterial, and venous). Use of extra lines for the management of postoperative complications thereby increases the risk of Staphylococcus epidermidis gaining access to the circulation. A subgroup of venous lines used to administer inotropic agents was found to be sterile on culture, and this was the result of the anti-oxidant (sodium metabisulphite) in the inotrope solution acting as an antiseptic.